2022
DOI: 10.3389/ffunb.2022.886685
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Protection Approaches Facilitate Conservation of Overlooked Fungal Diversity – A Case Study From the Norwegian Coastal Heathland System

Abstract: European coastal heathlands are distinct ecosystems shaped by land use tradition and they have experienced an 80% area reduction from their historical maximum. These mosaics of mires and wind exposed patches have ericaceous shrub dominated vegetation, and soils within coastal heathlands are characterized by low pH and high levels of recalcitrant debris. Using a culture-based approach with molecular identification of isolates, we characterized root-associated fungal communities of six ericaceous species in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Appreciation of the diversity of putative ErM colonizing Ericaceae roots has expanded recently (Bougoure et al 2007; Fehrer et al 2019) to include many ascomycetes in the order Helotiales (Walker et al 2011) and some basidiomycetes (Selosse et al 2007; Vohník et al 2012). A recent study of ErM diversity in Norwegian heathlands found several new ErM operational taxonomic units (OTUs) within both Ascomycota and Basidiomycota associating with heather roots (Blaalid & Davey 2022). Multiple ErM species often co‐colonize a single host plant (Gorzelak et al 2012) and their functionality, when combined, might become enhanced leading to increased resilience to environmental change (Perotto et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Appreciation of the diversity of putative ErM colonizing Ericaceae roots has expanded recently (Bougoure et al 2007; Fehrer et al 2019) to include many ascomycetes in the order Helotiales (Walker et al 2011) and some basidiomycetes (Selosse et al 2007; Vohník et al 2012). A recent study of ErM diversity in Norwegian heathlands found several new ErM operational taxonomic units (OTUs) within both Ascomycota and Basidiomycota associating with heather roots (Blaalid & Davey 2022). Multiple ErM species often co‐colonize a single host plant (Gorzelak et al 2012) and their functionality, when combined, might become enhanced leading to increased resilience to environmental change (Perotto et al 2002).…”
Section: Introductionmentioning
confidence: 99%